Harnessing stories of home in Fort Good Hope, Northwest Territories: Examining the role of housing and planning in advancing Indigenous self-determination - Pugsley, Aimee; Christensen, Julia (Canadian Planning and Policy / Aménagement et politique au Canada, 2026)
It is widely recognized that the housing landscape in northern Canada, characterized by chronic housing insecurity, homelessness, and inadequate policy responses, is in a state of crisis. In Fort Good Hope, a Dene First Nation in the Sahtu region of the Northwest Territories, the K'ásho Got’ı̨ne Housing Society is coordinating a community-led strategy to deliver their own housing and home. While their work supports the call for Indigenous self-determination, the systemic barriers that impede their efforts highlight the challenges of realizing self-determination in the current governance system. This paper draws on a series of interviews and archival research to explore how home, housing, and planning can support self-determination in northern and Indigenous communities. We problematize the stories of housing and planning that construct state dependencies and discursively limit possibilities for self-determination, elevating instead the story of home that empowers Fort Good Hope in its self-determination. Ultimately, we demonstrate the power for knowledge and identity production in housing and planning systems, and highlight the importance of challenging the settler colonial ontologies implicated in state-sanctioned approaches to self-determination.